The Triple Bottom Line in Language Tourism (Journal of Business, Universidad del Pacífico (Lima, Peru), 2025)
The sustainable development of language tourism must be supported by the use of specific indicators capable of measuring the economic, social and environmental aspects related to the sector’s activity, in line with the Triple Bottom Line (TBL) concept. This is in line with Goal 12 of the Sustainable Development Goals (SDGs), which determines the importance of adequate reporting in these areas, allowing to manage, plan and monitor actions and results by stakeholders and companies. Given the need to determine specific indicators for this tourism, an analysis of high-impact scientific publications on this topic has been carried out. Reports, studies and publications from various sources and official bodies, both public and private, have been reviewed. The paper identifies the main factors of language tourism and proposes a series of indicators for measuring its economic, social and environmental impact. Finally, a SWOT analysis of the sector is carried out. Our study has clear implications for managers of language tourism companies, as well as political authorities, who will have a base of reference indicators to determine the triple impact of language tourism. The study contributes to ensuring that these activities are socially responsible, respectful of the environment and contribute to the sustainable development of the regions visited.
Keywords: Language tourism, economic impact, social impact, environmental impact, Triple Bottom Line, indicators